2009
DOI: 10.1136/gut.2008.169656
|View full text |Cite
|
Sign up to set email alerts
|

Endocytotic segregation of gliadin peptide 31-49 in enterocytes

Abstract: Endocytic segregation of gliadin peptide AA 31-49 seems to be a constitutive process. It explains why this peptide cannot stimulate gluten-sensitive T cells. Presentation of gliadin peptides by HLA-DR proteins via late endosomes within enterocytes might induce a tolerogenic effect and constitutes a potentially promising therapeutic approach for induction of tolerance towards gliadin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
64
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 47 publications
5
64
0
8
Order By: Relevance
“…Antigens-MHC complexes are exposed on the basolateral membranes of enterocytes or released by exosomes to initiate and propagate the immune response [78]. In celiac disease, gliadin peptides with different toxicity/immunogenecity follow separate endocytic pathways, since peptides AA56-68 and AA229-246, but not gliadin peptide AA31-49, are found in HLA-DR-positive late endosomes [79]. Consequently antigen delivery and presentation on the basolateral membrane and immune response activation will be different for these peptides.…”
Section: Increased Antigen Uptake In Ibd and Celiac Diseasementioning
confidence: 99%
“…Antigens-MHC complexes are exposed on the basolateral membranes of enterocytes or released by exosomes to initiate and propagate the immune response [78]. In celiac disease, gliadin peptides with different toxicity/immunogenecity follow separate endocytic pathways, since peptides AA56-68 and AA229-246, but not gliadin peptide AA31-49, are found in HLA-DR-positive late endosomes [79]. Consequently antigen delivery and presentation on the basolateral membrane and immune response activation will be different for these peptides.…”
Section: Increased Antigen Uptake In Ibd and Celiac Diseasementioning
confidence: 99%
“…In fact, by interfering with endocytic trafficking (12,17), gliadin and P31-43 slow down the decay of activated EGFR (11), resulting in the proliferation of CaCo-2 cells and the crypt enterocytes from intestinal biopsy samples from patients with CD. The proinflammatory cytokine IL15 is also a major mediator of the innate immune response in CD (9,(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 98%
“…Zimmer et al 13 confirmed that both toxic and immunogenic peptides are internalised by the enterocytes, but they follow different endocytotic pathways, as shown by p31-49 which bypasses HLA-DR+ late endosomes and escapes antigen presentation at the basolateral membrane, though we do not know the fate of these peptides: are they translocated by a protected pathway, or degraded in endosomes? The authors hypothesised that HLA-DR+ enterocytes generate a tolerogenic effect in contrast to the immunostimulatory effect mediated by HLA-DQ+ lamina propria dendritic cells.…”
mentioning
confidence: 95%
“…In this issue of Gut , the papers by Luciani et al 12 (see page ) and by Zimmer et al 13 (see page ) focus on some of the unsolved questions of CoD pathogenesis. By using epithelial cell lines and human duodenal biopsies, the authors analysed the epithelial uptake and processing of gliadin peptides via intracellular compartments, which result in the activation of new signalling pathways of mucosal inflammation,12 and different routes of antigen presentation 13.…”
mentioning
confidence: 99%
See 1 more Smart Citation